Constructional ceramics on the basis of silicon carbide for the units of friction and details of oil-and-gas and chemical equipment - Криль, А.О.; Криль, Я.А.; Дрогомирецький, Я.М. (Problems of Tribology, 2014)
Conducted researches of processes of wear of ceramic materials on the basis of silicon carbide in the conditions of friction of sliding without oil and interaction with a gasabrasive stream. At the terms of dry friction it is set on air, that with the increase of speed of sliding and loading the coefficient of friction goes down, and intensity of wear grows. In the conditions of gasabrasive wear at the small angles of attack (α<30°) the silicon carbide is characterized the higher index of wear resistance by comparison to the hard metal of VK8. The prospects of application of silicon carbide are considered in the units of friction, details locking and regulating armature of oil-and-gas and chemical industries and aeroabrasive nozzles.